Identifikasi Tokoh Abdullah bin Saba’ Dalam Literatur Sunni dan Syi’ah - Al Hafidh Nasution (Jurnal Penelitian Medan Agama, 2018)
This paper tries to explain the history of Abdullah bin Saba 'which was perpetuated by the scholars because of its enormous role in the dark history of the people in the early days of Islam, in this case it has been written by classical Ulama in the Chronicles Sunni, such as Imam at Tabari in inbook Tarikhhisscholars, clerics and others. so also in the books of Shiite scholars. However, there are those who doubt the path of the transmission because only from one lane, Abdullah bin Saba is 'doubtful and declares that Abdullah bin Saba' is a prominent figure. It starts from the path of transmission which is in the book of Chronicles, only one path. Therefore, the author tries to examine the path of transmission in the book of the Date. This study uses the content analysis method. As a source of data used in the study of the truth of Abdulllah bin Saba 'figure, namely through the perspective of the Sunni and Shia books. The author tries to explain the results of research that shows that the figure of Abdullah bin Saba 'the fact of his existence and information obtained from Sunni and Shia data sources has similarities about the figure.